The Use of Documentary Video to Teach Writing News Item Text to the Tenth Grade Students in SMAN 4 Bangkalan (RETAIN, 2013)
Some people may find difficulties in writing something or express their ideas. They have a lot of ideas in their mind, but they cannot decide what they want to write. When the first problem solved, other problem appear that they do not know how to write correctly. Those difficulties faced by students, too and make them frustated and not confident in writing. The teacher has a job to give some stimulus and let the students’ imagination free by not forcing the students directly to write and not giving them the same boring strategy all the time. The teacher can use a video in teaching. The combination of audio and visual media that presented by a video, can help the students to be more interested in the material and have them get some new ideas, especially can release the boredom. In this case, the teacher asked the students to write composition of news item based on the documentary video. The research is a descriptive qualitative and the objective of this study to find out how the documentary video is applied in teaching writing of news item, the students’ writing ability, and the students’ responses toward the documentary video. The subject of this research was the tenth grade students of SMA Negeri 4 Bangkalan which consisted of 36 students in class X-1. The instruments that are used by the researcher are observation checklist, students’ tasks and questionnaire. The data which are obtained in this research will be served in the form of sentences. Based on the analysis data, the researcher collected the data from three observations. The first observation, teacher did not play the video and the students were not asked to write composition. In the second and third observations the teacher played documentary video and the students were asked to write composition based on the documentary video. The students’ tasks were analyzed using ESL composition profile which contains elements of writing. Those were described whether its categories were very good, good, fair, and poor criteria. In the last meeting, the researcher gave questionnaire to know students’ response towards the documentary video. In conclusion, the researcher found that video was a helpful medium to release boredom and made the students understood about the material easily. The result of the students’ tasks indicated that their ability in writing increased. Though, it was not significant, but, still There were progress from the students’ writing in terms of content, organization, vocabulary, language use and mechanic. Most of the students gave a positive responses toward the use of documentary video. Key Words: Video, Documentary video, teaching writing, news item text, learning medium. Abstrak Beberapa orang menemukan kesulitan dalam menulis sesuatu atau mengekspresikan ide mereka. Mereka memiliki banyak ide dalam pikiran mereka, namun mereka tidak mampu memutuskan apa yang ingin ditulis. Ketika masalah tersebut teratasi, muncul masalah lain, yaiitu mereka tidak mampu menulis dengan benar. Masalah-masalah tersebut juga dihadapi oleh para siswa dan mengakibatkan mereka frustasi serta tidak memiliki kepercayaan diri dalam menulis.Oleh sebab itu, guru memiliki tugas untuk memberikan stimuli dan membebaskan imaginasi mereka dengan tidak memaksa mereka untuk secara langsung menulis dan tidak menggunakan strategi membosankan yang sama dalam mengajar. Guru dapat menggunakan media video dalam pembelajaran. Kombinasi media suara dan gambar yang ditampilkan, dapat membantu para siswa lebih tertarik kepada materi yang diberikan dan memunculkan ide-ide baru, terutama juga untuk menghilangkan kebosanan. Dalam hal ini, guru memberikan perintah kepada para siswa untuk menulis komposisi news item berdasarkan video dokumentasi. Penelitian ini menggunakan method descriptif qualitative dan tujuan penelitian ini adalah bagaimana penerapan video dokumentasi dalam pembelajaran menulis news item, untuk mengetahui kemampuan siswa dalam menulis, serta respon siswa terhadap video dokumentasi. Subjek dari penelitian ini adalah siswa kelas X SMAN 4 Bangkalan yang terdiri dari 36 siswa dikelas X-1. Instrumen penelitian yang digunakan oleh peneliti adalah form observasi, tugas siswa, beserta kuesioner. Data yang didapat kemudian akan disajikan dalam bentuk kalimat. Berdasarkan data analisis, peneliti mengumpulkan data dari tiga pertemuan. Pada pertemuan pertama, guru tidak menampilkan video dokumentasi dan siswa tidak diminta untuk menulis komposisi. Pada pertemuan kedua dan ketiga, guru menampilkan video dokumentasi serta meminta siswa untuk menulis komposisi berdasarkan video dokumentasi tersebut. Tugas siswa di analisis menggunakan ESL composition profile yang berisi lima elemen dalam menulis. Penilaian tugas siswa tersebut dijelaskan dalam criteria sangat baik, baik, cukup dan kurang. Pada pertemuan terakhir, peneliti menyebarkan kuesioner untuk mengetahui respon siswa terhadap video dokumentasi. Pada kesimpulannya, peneliti menemukan bahwa video dapat membantu siswa dalam menghilangkan kebosanan serta mempermudah siswa menangkap materi yang diberikan. Hasil tugas siswa memperlihatkan bahwa kemampuan menulis mereka meningkat. Walaupun peningkatan tersebut tidak cukup signifikan, tetapi tetap ada kemajuan dari kemampuan menulis siswa berdasarkan isi, organisasi, kosakata, grammar, serta mechanic. Hampir seluruh siswa memberikan respon yang positif terhadap penggunaan video documenter. Kata Kunci: Video, video dokumentasi, pengajaran menulis, teks news item, media pengajaran